Criminalization of Sex Workers from the Perspective of Criminal Law Transformation in Indonesia - Hamdani Hamdani; Wieke Dewi Suryandari; Mohamad Tohari (Dinasti Research, 2024)
This research examines the phenomenon of the criminalization of sex workers in Indonesia amidst the ongoing transformation of criminal law. The criminalization of commercial sex workers (CSWs) often stems from social and moral norms that deem this practice immoral and illegal. This study aims to analyze the impact of criminalization on human rights and the welfare of CSWs, as well as how legal ambiguities contribute to the exploitation and violence they face. Additionally, it explores weaknesses in existing legal regulations and proposes necessary reform efforts to create a more inclusive legal framework that protects the basic rights of CSWs. Through a comprehensive approach, this research is expected to contribute to the development of more humane and effective policies, as well as enhance public understanding concerning the position and rights of CSWs in Indonesia.